Jews, Gentiles, and ethnic reconciliation: Paul's Jewish identity and Ephesians - Yee, Tet-Lim N. (Society for New Testament Studies monograph series, 2005)
Much scholarship has focused on Paul's insistence on Gentile membership of the people of God equally with Jews. Dr Yee's study of Ephesians 2 reveals how the distinctively Jewish world view of the author of Ephesians underlies this key text. He explores how the Ephesians' author provides a resolution to one of the thorniest issues regarding two ethnic groups in the earliest period of Christianity: can Jew and Gentile, the two estranged human groups, be one (people of God) and if so, how? Setting Ephesians 2 as fully as possible into its historical context, he describes some of the relevant Jewish features and demonstrates them, revealing many explosive but hidden issues. This book provides an important contribution to the continuing reassessment of Christian and Jewish self-understanding in regard to each other during the critical period of the latter decades of the first century CE.